Sjogren’s disease - symptoms, clinical signs and treatment - Carteron, Nancy (Henry Stewart Talks, 2016)
Sjogren’s disease: symptoms, Gastrointestinal, Ear-Nose-Throat, Pulmonary, Musculoskeletal, Cardiovascular, Vascular, Renal, Endocrine, Genitourinary, Dermal, Neurological, Haematological, Laboratory findings, Treatment, Prognosis
Archived at 2021/08/29